IMPLEMENTASI STANDAR PROSES DALAM KURIKULUM 2013 DI SEKOLAH DASAR - Ndaru Mukti Oktaviani; Isnaini Wulandari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Educational development through education must be adjusted to the needs of the community. Changes in the learning process under the 2013 Curriculum have significantly affected teachers’ readiness to implement it in schools. Based on the results of a Focus Group Discussion (FGD) conducted with elementary school teachers in the Kuningan region, it was found that most teachers still experience difficulties in implementing learning processes in accordance with the 2013 Curriculum. These findings indicate the need for further investigation into the factors causing teachers’ difficulties in applying the curriculum-based learning process. Therefore, this study aims to examine the implementation of process standards in the 2013 Curriculum at the elementary school level. This research employed a case study method and was conducted at public elementary schools in Kuningan Regency, namely SD Negeri Dukuhdalem (Japara District), SD Negeri 1 Manislor (Jalaksana District), and SD Negeri 1 Purwawinangun (Kuningan District). The research instruments used were observation sheets and interview guides. The results of the study indicate that the main obstacles in implementing the syllabus under the 2013 Curriculum include a lack of socialization regarding changes in syllabus content, teachers’ difficulties in preparing lesson plans—particularly in incorporating activities aligned with the scientific approach—and discrepancies between the required learning materials and those provided in textbooks. In terms of classroom management, teachers faced challenges related to their limited readiness to adapt to changes in the learning process. Furthermore, in the assessment aspect, most teachers reported difficulties due to the complexity of the assessment system and the limited availability of assessment instruments. These findings suggest that teachers still encounter significant challenges in fully implementing the learning and assessment processes mandated by the 2013 Curriculum.